2018
DOI: 10.1093/nar/gky096
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-dependent mechanism for transient expression of bacterial translocation filaments

Abstract: The prokaryotic RNA chaperone Hfq mediates sRNA–mRNA interactions and plays a significant role in post-transcriptional regulation of the type III secretion (T3S) system produced by a range of Escherichia coli pathotypes. UV-crosslinking was used to map Hfq-binding under conditions that promote T3S and multiple interactions were identified within polycistronic transcripts produced from the locus of enterocyte effacement (LEE) that encodes the T3S system. The majority of Hfq binding was within the LEE5 and LEE4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 61 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…Lately, it was reported that in the E. coli enterocyte effacement locus (LEE) Hfq plays a repressive and CsrA an activating role on sepL mRNA [52]. However, since the motif required for CsrA binding overlaps the second Hfq interaction site, binding of both chaperones is mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, it was reported that in the E. coli enterocyte effacement locus (LEE) Hfq plays a repressive and CsrA an activating role on sepL mRNA [52]. However, since the motif required for CsrA binding overlaps the second Hfq interaction site, binding of both chaperones is mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…6E). sepL is the first gene in LEE4, and several studies indicated that expression of the entire operon is dependent on its transcription and translation (111,(124)(125)(126) (Fig. 6E).…”
Section: Specific Mechanisms Of Virulence Factor Regulationmentioning
confidence: 97%
“…The expression and activity of Ler, GrlA, and GrlR are a hub of regulation at all levels within the cell. A recent study provided evidence that Hfq binds multiple RNA transcripts throughout the LEE, including LEE1 and grlRA (111). Although the authors extensively characterized the involvement of Hfq in expression of LEE4 (detailed below), no data describing the specific mechanism of Hfq-dependent regulation of Ler or GrlA expression were reported in that study.…”
Section: Specific Mechanisms Of Virulence Factor Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of these sRNAs on grlRA is dependent on Hfq, a bacterial RNA chaperone that mediates interactions between sRNA and mRNA. Hfq was recently found to bind to LEE4 and LEE5 operons, suggesting a way for sRNAs to influence T3SS regulation (Wang et al, ). There is also evidence of regulation by sRNAs in other T3SS‐expressing pathogens, such as Yersinia pseudotuberculosis , Yersinia pestis , and S .…”
Section: Fluidity Of T3ss Expression Is Crucial For Within‐host Adaptmentioning
confidence: 99%